Higher Dietary Protein Intake is Associated with Lower Body Fat in the Newfoundland Population - Green, Kristian K. (Libertas Academica, 2010)
BACKGROUND: Increased protein proportions in the diet combined with energy restriction has been shown to enhance weight loss during dietary intervention. It is not known if the beneficial effect of dietary protein exists in the general population under normal living conditions without a negative energy balance. METHODS: A total of 1834 participants (n = 443 men, n = 1391 women) were recruited from the CODING study. Participants’ dietary macronutrient compositions were determined through a Willett FFQ. Body composition variables including percent body fat (%BF), percent trunk fat (%TF), percent total lean mass (%LM), and percent trunk lean mass (%TLM) were determined using DXA. Major confounding factors including age, physical activity levels, total caloric intake, carbohydrate intake, menopausal status, smoking status and medication use were controlled for in all analyses. RESULTS: Significant inverse relationships were observed between dietary protein intake (g/kg body weight/day) and weight, waist circumference, waist-to-hip ratio, BMI, %BF, and %TF (P < 0.001). Significant positive relationships were observed with %LM and %TLM (P < 0.001). Additionally, significant differences in weight (12.7 kg in men, 11.4 kg in women), BMI (4.1 BMI units in men, 4.2 units in women), and %BF (7.6% in men, 6.0% in women) were observed between low and high dietary protein consuming groups (P < 0.001). Dietary protein explained 11% of the total variation in %BF in the NL population. CONCLUSION: This study provides strong evidence that higher protein intake, even in the absence of energy restriction, is associated with a more favorable body composition in the general population.